2020
DOI: 10.21203/rs.3.rs-41684/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nomogram to identify severe Coronavirus Disease 2019 (COVID-19) based on initial clinical and CT characteristics: a multi-center study

Abstract: Background: To develop and validate a nomogram for early identification of severe coronavirus disease 2019 (COVID-19) based on initial clinical and CT characteristics.Methods: The initial clinical and CT imaging data of 217 patients with COVID-19 were analyzed retrospectively from January to March 2020. 217 patients with 146 mild cases and 71 severe cases were randomly divided into training and validation cohorts. Independent risk factors were selected to construct the nomogram for predicting severe COVID-19. … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…To our knowledge, only two recent retrospective studies have proposed the construction of a nomogram in order to identify the predictors of severe coronavirus disease [47,48]. The first study used multivariate analysis to evaluate various clinical and laboratory parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only two recent retrospective studies have proposed the construction of a nomogram in order to identify the predictors of severe coronavirus disease [47,48]. The first study used multivariate analysis to evaluate various clinical and laboratory parameters.…”
Section: Discussionmentioning
confidence: 99%
“…However, the author did not include CT imaging among the risk indicators [47]. In contrast, CT was considered in the second paper, where initial clinical data and CT imaging data were evaluated in 217 COVID-19 patients [48]. Patients were classified into two groups; mild and severe disease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in many studies that the lesions in COV-ID-19 pneumonia classically show a more peripheral distribution (7,9). In the literature, there are data showing that the central or diffuse distribution is more common in cases with a severe prognosis (15). Therefore, we believed that the distribution characteristic on admission CT might change the predictive value of the CT score.…”
Section: Discussionmentioning
confidence: 88%
“…In another study investigating the predictive value of CT score as to mortality and disease severity, the parameter of age and high CT score were shown to be independent predictors of death and severity of the disease (6). In a study by Yu et al, multivariate logistic regression analysis showed that the lung severity score calculated by age, lesion density, and involvement rate were independent predictors for predicting the severity of the disease, while the presence of accompanying comorbidity was not a predictive factor (15). In our study, the score detected from admission CT was higher in the males and elderly included in the cytokinestorm group.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are studies proposing nomograms and/or different models to predict serious illness or death in COVID-19 patients [ 19 , 21 , 22 , 24 , 25 , 35 37 ]. Age was reported as a predictor for severe COVID-19 or mortality in previous studies and is included in most of the prediction models [ 16 – 21 , 24 , 25 , 32 , 35 , 38 , 39 ]. We found an increased risk of severe infection requiring ICU admission in the patients 56.5 years of age and older.…”
Section: Discussionmentioning
confidence: 99%